Artificial Intelligence and Democracy - Duberry, Jérôme (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This insightful book explores the citizen-government relation, as mediated through artificial intelligence (AI). Through a critical lens, Jérôme Duberry examines the role of AI in the relation and its implications for the quality of liberal democracy and the strength of civic capacity.